2012
DOI: 10.1002/hpm.2116
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards universal coverage with malaria control interventions: achievements and challenges in rural Burkina Faso

Abstract: This paper reports on a study, which assessed coverage with malaria control interventions in rural Burkina Faso, namely insecticide-treated mosquito nets (ITN) ownership, intermittent preventive treatment (IPTp) for pregnant women and artemisinin-based combination therapy (ACT) for under-five children. The study also addressed the distributional impact of such interventions, with specific reference to equity. The study used data from a representative household survey conducted on 1106 households in the Nouna H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 75 publications
1
25
0
1
Order By: Relevance
“…25 Coverage with insecticide-treated bed nets (ITNs) and artemisinin-based combination therapies (ACT) has much increased over the study period. 12,13 As malaria is the main cause of mortality in the second half of infancy and as roughly half of all childhood mortality is attributed to malaria in the study area, 26,27 increasing access to and use of malaria interventions will likely have played a major role with regard to the observed mortality effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Coverage with insecticide-treated bed nets (ITNs) and artemisinin-based combination therapies (ACT) has much increased over the study period. 12,13 As malaria is the main cause of mortality in the second half of infancy and as roughly half of all childhood mortality is attributed to malaria in the study area, 26,27 increasing access to and use of malaria interventions will likely have played a major role with regard to the observed mortality effects.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] It is of interest to know whether these interventions have improved infant survival in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The health system, which is already finding it very difficult to cope with malaria [20], is not prepared to contend with dengue fever. Health workers, mainly nurses and nurse assistants in both the public and private sectors, are not sufficiently trained for syndromic case management of dengue.…”
mentioning
confidence: 99%
“…Finally, the effort to control the vector, abandoned many years ago in Burkina Faso, must absolutely be revived, because it is one of the most effective means of dealing with the problem while waiting for a vaccine or another effective dengue control strategy [18]. The State and its technical and financial partners need to mobilize now so that the health system and its public health interventions can begin working on the most effective management of dengue fever [20].…”
mentioning
confidence: 99%
“…This suggests a possible study effect owing to the availability of AL for all confirmed cases of symptomatic malaria and the provision of an LLIN to every participant in the study. A recent study, which examined the coverage of malaria control interventions in Burkina Faso, reported that 59% of households in the study population owned an insecticide-treated bednet (ITN) and only 34% of children under 5 years of age with a reported malaria case were treated with an artemisinin-based combination therapy (ACT) [23]. It is, therefore, possible that receipt of an LLIN by every study participant increased the use of ITNs in both study arms.…”
Section: Discussionmentioning
confidence: 99%